Comparative evaluation of erosive potential of various frozen and unfrozen fruit juices on primary teeth enamel: An in vitro study - Sunil T Philip; Anshad M Abdulla; Sivadas Ganapathy; Vaishnavi Vedam; Vini Rajeev (Wolters Kluwer Medknow Publications, 2019)
Background: Changing lifestyle pattern and food habits has a deteriorating effect on dental tissues. Dental erosion is a pathological wear of hard tissues of teeth with increased consumption of acidic and carbonated drinks. Susceptibility to erosion in primary dentition is more compared to permanent dentition due to softer and disordered crystal structure of enamel. Objectives: The main aim of the study was to determine and compare the erosive potential of different fruit juices in frozen/unfrozen forms on primary teeth by studying the calcium dissolution. Materials and methods: pH of four different juices (pure) - apple, orange, citrus limetta (musumbi) and grapes were determined using a digital pH meter. The titratable acidity of these in frozen and unfrozen forms were determined by adding 0.2 ml of 1M NaOH to these to raise to pH=5.5(critical pH) and pH =7(neutral pH). Forty eight caries free deciduous anterior teeth specimens were prepared to study the calcium dissolution by atomic absorption spectrophotometer. The results were analysed for statistical significance using One-way Repeated Measures ANOVA and pair wise multiple comparison with Bonferroni correction. Results: Total titratable acidity and calcium dissolution were found to be significantly more in the initial thawed fruit juices. Conclusion: Frozen fruit juices had more buffering capacity and erosive potential than unfrozen forms. The study concluded that sucking on frozen fruit juices is more damaging to teeth than unfrozen forms because more of erosion is expected to occur in a frozen state.